THE EFFECT OF E-WOM, BRAND IMAGE, MEDIATED BY TRUST ON SHOPEE CONSUMER PURCHASE INTENTION (STUDY ON GENERATION X OF TELUK PUCUNG VILLAGE) - Resti Meliana Putri; Rianto, Muhammad Richo; Choiroel Woestho (Draf Solusi Indonesia, 2024)
A Quantitative descriptive approach, and this study has a sample of 100 survey respondents in generation X, who have used and downloaded Shopee in Teluk Pucung Village. The analysis tool uses SmartPLS 4.0 for hypothesis testing and the feasibility of research methods. This sampling technique uses Non-Probability Sampling techniques, the data is collected using a questionnaire. The results showed that 1. EWOM has a positive and significant effect on trust; 2. Brand Image has a positive and significant effect on Trust; 3. Trust has a positive and significant effect on Purchase Intention; 4. EWOM has a positive and significant effect on Purchase Intention; 5. Brand Image has a positive and significant effect on Purchase Intention; 6. E-wom has a positive effect on Purchase Intention mediated by Trust; 7. Brand Image has a positive effect on Purchase Intention mediated by Trust. This limitation is the object of research conducted by generation X Shopee users in Teluk Pucung Village, so that it can be used as a suggestion for future researchers.